Menuju Kota Malang Zero Stunting - Brilian Ramadlan, Khoirus Syifa; Hayat, Hayat; Putra, Langgeng Rachmatullah (Idarotuna : Journal of Administrative Science, 2025)
According to Edward III's policy implementation model, which focuses on four key elements—communication, resource availability, implementers' attitudes, and bureaucratic structure—this study examines the Zero Stunting policy's implementation in the Malang City Health Office. The study's primary goals are to assess how well the Zero Stunting policy has been applied and to pinpoint any roadblocks that may be affecting the field's implementation process. In-depth interviews, observations, and documentation studies were used to gather data for this descriptive qualitative study. According to the research findings, regular socialization and the use of a variety of communication platforms have demonstrated that the communication between policy makers and implementers in the field has been going rather smoothly. Resources are generally sufficient, however implementers must deal with tasks that overlap with those of other programs, which affects how well they are implemented. The implementers, however, maintain vigilance and operate the program as efficiently as possible. Although there are currently implementation irregularities in a number of work areas, the majority of implementers exhibit a strong commitment in terms of disposition. Although a cross-sector coordination-supporting bureaucratic framework has been established, its execution has not been entirely successful because of overlapping authorities and a lack of data integration. Therefore, to guarantee the sustainability and efficacy of the Zero Stunting policy in Malang City, it is imperative to build human resource capacity, improve sectoral synergy, and carry out regular evaluations.